Catalytic transesterification of beta-ketoesters with zeolite H-FER under solvent free conditions - Chavan, Subhash P.; Pasupathy, K.; Shengule, S.; Shinde, V.; Anand, R. (Arkivoc, 2005)
Zeolite H-FER catalyzes the transesterification of beta-ketoesters with variety of alcohols under solvent-less condition in excellent yields. The catalyst can be reused without any loss of activity.
Keywords: ferrierite; transesterification; zeolite

Convenient formal synthesis of (+/-)-paroxetine - Chavan, Subhash P.; Khobragade, Dushant A.; Pathak, Ashok B.; Kalkote, Uttam R. (Synthetic Communications, 2007)
A formal total synthesis of antidepressant (+/-)-paroxetine employing a solvent-free Heck reaction is disclosed.
Keywords: antidepressants; carbamate; electrophile; Heck reaction; piperidines

Convenient formal synthesis of (2S,3S)-3-hydroxy pipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Dumare, Nilesh B.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2011)
A convenient synthesis of (2S,3S)-3-hydroxy pipecolic acid starting from inexpensive and easily available L-(+)-tartaric acid has been described. (C) 2011 Elsevier Ltd. All rights reserved.

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2014)
The efficient and practical formal syntheses of both enantiomers of cis 3-hydroxypipecolic acid were accomplished from cis aziridine-2-carboxylate as the common synthetic precursor. The key steps involved are stereo and regioselective aziridine ring opening, reductive cyclization and selective N-debenzylation over O-debenzylation reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxypipecolic acid; Aziridine ring opening; Aziridine-2-carboxylate; Piperidine alkaloids; Selective debenzylation

Chirality induction and chiron approaches to enantioselective total synthesis of alpha-lipoic acid - Chavan, Subhash P.; Pawar, Kailash P.; Praveen, Ch; Patil, Niteen B. (Tetrahedron, 2015)
An efficient, short and convenient asymmetric synthesis of (R)-(+)-lipoic acid in seven steps from chiral hydroxy aldehyde with 32.5% overall yield is described. Synthesis of S and R enantiomers of a-lipoic acid from cis-1,4-butene diol derived chiral lactone is reported with 34 % overall yield. The present synthesis involves use of simple reaction conditions making it a convenient synthesis. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool; Chirality induction; enantioselective; Lipoic acid; sharpless asymmetric dihydroxylation

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid (vol 55, pg 6423, 2014) - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2020)

cis-aziridine synthon based synthetic investigation for tamiflu employing horner-wadsworth-emmons reaction - Chavan, Subhash P.; Kawale, Sanket A.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2022)
Synthetic investigations to achieve a novel intermediate of Tamiflu by using cis-aziridine as a chiral building block, which is readily synthesized from (D)-mannitol as a renewable starting material, has been presented. The present approach utilizes the intramolecular Horner-Wadsworth-Emmons reaction as the key step for the synthesis of Tamiflu. On the other hand, diene containing allylic aziridine framework is found to be inefficient to furnish the six-membered core skeleton of Tamiflu through ring-closing metathesis reaction.
Keywords: Aziridine; cyclization; HWE reaction; Metathesis; Tamiflu